Review of 'Too Hot To Touch: The Problem of High‐Level Nuclear Waste' by William M. Alley and Rosemarie Alley. Issue 2 (11th November 2013) - Kwicklis, E. M.
<x xml:space="preserve">Abstract</x> "Too Hot to Touch" by Bill and Rosemarie Alley chronicles the intermittent 60‐year effort by the federal government to find a permanent solution for the disposal of high‐level nuclear waste. It is a fascinating and well‐told story that draws on a combination of public media and government reports. It is not optimistic that a solution to the problem will soon be found given the social, political, and technical challenges.<boxed-text content-type="graphic" id="gfl12068-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>